Assessment of knowledge of school going children regarding HIV/AIDS in rural field practice area (RHTC) Srinagar, JLN medical college and Hospital, Ajmer - Keswani, Mahesh; Gupta, Teena; Meharda, Bharat (International Journal Of Community Medicine And Public Health, 2019)
Background: AIDS, the acquired immune-deficiency syndrome (slim disease) is a fatal illness caused by a retro virus known as the human immunodeficiency virus (HIV) which breaks down the body’s immune system. Transmission of HIV is mainly by unprotected sexual contacts, mother to child (antenatal, perinatal and postnatal), and transfer of infected blood. Methods: The present cross-sectional study was conducted from January 2018 to June 2018 in randomly selected government and private schools from rural field practice area. A total of 300 students randomly selected from 10th to 12th class were included in the study, of whom 150 were boys and 150 were girls. The data collected were presented in percentage and figure. Results: Majority of students (61.35%) belonged to age group of 15-18 years and most of them were females. Most of the students (85.2%) had heard about HIV/AIDS but only 53.5% knew that HIV/AIDS caused by a virus. The knowledge regarding mode of transmission of HIV/AIDS was unprotected sex, as expressed by 86.1% students. 70.66% students believe that condoms is the best method of protection against HIV followed by safe blood 43.6%, Disposable syringes 40.29%. Conclusions: Majority of students (61.35%) belonged to age group of 15-18 years and most of them were females. Most of the students (85.2%) had heard about HIV/AIDS but only 53.5% knew that HIV/AIDS caused by a virus. The knowledge regarding mode of transmission of HIV/AIDS was unprotected sex, as expressed by 86.1% students. 70.66% students believe that condoms is the best method of protection against HIV followed by safe blood 43.6%, Disposable syringes 40.29%.